Investigations of Phase Transformation in Monocrystalline Silicon at Low Temperatures via Nanoindentation - Shunbo Wang (Nature Portfolio, 2017)
Abstract Nanoindentations of monocrystalline silicon are conducted to investigate the phase transformation process at a temperature range from 292 K to 210 K. The load-displacement curves are obtained and the residual indents are detected by Raman spectra. MD simulations are also conducted to identify the phase state during nanoindentation. The results show that the low temperature has no influence on the generation of Si-II during loading process of indentation, but the phenomenon of pop-out is inhibited with the temperature decreasing. The probability of pop-out occurrence has a dramatic drop from 260 K to 230 K. Both the generation and propagation of Si-III/XII transformed from Si-II are inhibited by the low temperature, and only a-Si was generated as a final phase state.